2021
DOI: 10.7554/elife.62206
|View full text |Cite
|
Sign up to set email alerts
|

Biological constraints on GWAS SNPs at suggestive significance thresholds reveal additional BMI loci

Abstract: To uncover novel significant association signals (p<5×10−8), genome-wide association studies (GWAS) requires increasingly larger sample sizes to overcome statistical correction for multiple testing. As an alternative, we aimed to identify associations among suggestive signals (5 × 10−8≤p<5×10−4) in increasingly powered GWAS efforts using chromatin accessibility and direct contact with gene promoters as biological constraints. We conducted retrospective analyses of three GIANT BMI GWAS efforts using ATAC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
(33 reference statements)
0
35
0
Order By: Relevance
“…Genome‐wide association studies (GWAS) have revealed that human AC3 (hAC3) is associated with obesity. [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] To examine the function of human AC3 (hAC3) in regulating body weight, we generated a humanized mouse by introducing the complete hAC3 sequence into the Rosa26 site in the mouse genome (Figure S1 , Supporting Information). The resulting humanized AC3 knock‐in mice (hAC3 mice) were fertile and healthy throughout their lifespan.…”
Section: Resultsmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) have revealed that human AC3 (hAC3) is associated with obesity. [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] To examine the function of human AC3 (hAC3) in regulating body weight, we generated a humanized mouse by introducing the complete hAC3 sequence into the Rosa26 site in the mouse genome (Figure S1 , Supporting Information). The resulting humanized AC3 knock‐in mice (hAC3 mice) were fertile and healthy throughout their lifespan.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, SNPs that meet the suggestive threshold but not the GWAS threshold in some cases have at times been shown to be GWAS significant (i.e. p<5 × 10 −8 ) after further study with a larger sample size [ 38 , 39 ]. Thus, it may be useful and informative to examine the biological role of SNPs that are in this range of p values, especially with regard to a potential regulatory role and keeping in mind that we had a relatively small sample size [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…To be included in further enrichment and annotation analyses, the meta-analytic p-value had to be below 1 × 10 −5 . We chose this threshold because previous studies have shown that some variants that do not meet the GWAS threshold may still have important regulatory or biological functions in some cases and may be worthy of further study and follow-up, especially in the context of gene regulation [59,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The MTBC L4.6/Uganda is the most recently evolved of the three, a sub-lineage of the MTBC L4 generalist lineage, and is unique to this part of Africa [4,9]. SNP and LSP-based phylogeny have been proven to be consistent in multiple studies of MTBC sub-lineages, and the body of literature on MTBC lineages indicates that this is an excellent method for differentiating the MTBC L4 sub-lineages [6,28,59]. Low sequence variation and the lack of horizontal transfer make SNPs and LSPs a method well-suited to distinguish lineages, and this approach has been previously validated and published [6,12,13].…”
Section: Determination Of Mtb Lineagementioning
confidence: 99%